1990
DOI: 10.1289/ehp.908679
|View full text |Cite
|
Sign up to set email alerts
|

Overview of reproductive and developmental toxicity studies of 1,3-butadiene in rodents.

Abstract: A series of studies to further evaluate the developmental and reproductive toxicity of inhaled 1,3-butadiene was sponsored by the National Toxicology Program. Pregnant Sprague-Dawley rats (24-28/group) and Swiss (CD-1) mice (18-22/group) were exposed to atmospheric concentrations of 0, 40, 200, or 1000 ppm 1,3-butadiene for 6 hr/day on days 6 through 15 of gestation (dg) and killed on dg 18 (mice) or dg 20 (rats). Subsequently, the uterine contents were evaluated; individual fetal body weights were recorded; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…37 Acute toxicity per se was not assessed but LC 50 values could not be lower than the no effect levels in repeated exposure studies. c Critical values for 1,3-butadiene are taken from Owen and Glaister (repeated dose toxicity), 44 Morissey et al (developmental toxicity), 45 and WIL Research (reproductive toxicity). 008006-14-2 Natural gas Raw natural gas, as found in nature, or a gaseous combination of hydrocarbons having carbon numbers predominantly in the range of C 1 through C 4 separated from raw natural gas by the removal of natural gas condensate, natural gas liquid, and natural gas condensate/natural gas.…”
Section: Petroleum Hydrocarbon Gases Category Members By Casrnmentioning
confidence: 99%
“…37 Acute toxicity per se was not assessed but LC 50 values could not be lower than the no effect levels in repeated exposure studies. c Critical values for 1,3-butadiene are taken from Owen and Glaister (repeated dose toxicity), 44 Morissey et al (developmental toxicity), 45 and WIL Research (reproductive toxicity). 008006-14-2 Natural gas Raw natural gas, as found in nature, or a gaseous combination of hydrocarbons having carbon numbers predominantly in the range of C 1 through C 4 separated from raw natural gas by the removal of natural gas condensate, natural gas liquid, and natural gas condensate/natural gas.…”
Section: Petroleum Hydrocarbon Gases Category Members By Casrnmentioning
confidence: 99%
“…Butadiene was a clear developmental toxicant in mice, producing a reduction in mean fetal weight (59). These studies have been the subject of a recent, intensive review (60).…”
Section: Developmental Toxicitymentioning
confidence: 99%
“…Studies conducted at Battelle Northwest Laboratories (15)(16)(17) have demonstrated that butadiene is maternally toxic to Sprague-Dawley rats at 1000 ppm. However, there is no developmental toxicity observed in the rat fetuses even at doses where maternal toxicity is observed.…”
Section: Toxicitymentioning
confidence: 99%
“…A reduction in the weight of male mouse fetuses was also observed at 40 ppm, but no maternal toxicity was evident. After exposure to 200, 1000, or 5000 ppm for 5 days, there was a concentration-related increase in abnormal sperm in male B6C3F1 mice (17). The immunotoxicity of butadiene was examined in male B6C3F1 mice exposed to 1250 ppm (6 hr/day, 5 days/week) for 12 weeks (18).…”
Section: Toxicitymentioning
confidence: 99%